Smart, Age-Friendly Cities and Communities: The Emergence of Socio-Technological Solutions in the Central and Eastern Europe - Andrzej Klimczuk; Łukasz Tomczyk (Active and Assisted Living: Technologies and Applications, 2016)
The chapter aims to introduce an integrated approach to concepts of (1) smart cities and (2) age-friendly cities and communities. Although these ideas are widely promoted by the European Union and the World Health Organisation, they are perceived as separate. Meanwhile, these concepts are closely intermingled in theory and practise concerning the promotion of healthy and active ageing, a universal design, usability and accessibility of age-friendly environments, reducing of the digital divide and robotic divide, and reducing of older adults' social isolation. The conclusion underlines the need for participatory creation of ambient assisted living (AAL) technologies and applications with older adults and the need for advocacy to promote AAL in the context of the silver economy especially in the Central and Eastern Europe.
Keywords: P25; J14; J18; 330; Smart Cities; Age-Friendly Cities and Communities; Ageing in Place 2.0; Age-Friendly Environments; Aids for Activities of Daily Living; Universal Design